Energetic aminated-azole assemblies from intramolecular and intermolecular N–H⋯O and N–H⋯N hydrogen bonds. Issue 52 (8th June 2016) - He, Chunlin; Yin, Ping; Mitchell, Lauren A.; Parrish, Damon A.; Shreeve, Jean'ne M.
Abstract : Extensive H-bond interactions in four aminated azoles give them comprehensive properties, such as high density, good thermal stability and reasonable sensitivity as well as high detonation performance. Abstract : Compounds with adjacent C–NO2, C–NH2 and N–NH2 groups were designed and synthesized via amination. Their structures were characterized by infrared, and multinuclear NMR spectroscopy, elemental analysis, and X-ray single crystal diffraction. The effect of intramolecular and intermolecular N–H⋯O and N–H⋯N hydrogen bonds is discussed. Detonation properties were calculated by EXPLO 5 software based on calculated HOFs and experimental densities.